Evolution of the Post-Barreiras Sediments in the coastal zone of São Luís Basin, Maranhão, Brazil - Rossetti, Dilce de Fátima; Rocca, Renê Rojas; Tatumi, Sonia Hatsue (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2013)
The Post-Barreiras Sediments have been poorly studied,despite their interest for reconstituting sea-level fluctuations and the tectonic history in the Quaternary. These strata record more than a single depositional episode, which remain to be investigated. This work presents the results of optically stimulated luminescence (OSL) of the Post-Barreiras Sediments exposed in the littoral of the State of Maranhão, Brazil. The ages indicate deposition between the Late Pleistocene and Late Holocene. Three sedimentary successions were recorded between 84,000 and 38,000 years, 29,000 and 16,000 years, and 11,000 and 500 years. Succession 1, which is the oldest one, started after the Last Interglacial, being coincident with the high frequency-rise in sea level between 84,000 and 70,000 years, and might include a marine contribution. The remainder of this succession, as well as succession 2, occurred during the sea-level fall that culminated with the Last Glacial Maximum. These deposits are related to the aeolian sand reworking of coastal dunes exposed in the littoral. Succession 3 was formed during the sea-level rise that culminated with the mid-Holocene transgression. Only deposits formed in coastal dunes were recorded in this succession. These deposits filled depressions and embayment in the Barreiras Formation, and eventually advanced over areas where this unit is topographically elevated.